2009
DOI: 10.1007/s11934-009-0060-5
|View full text |Cite
|
Sign up to set email alerts
|

Bone-anchored suburethral sling: Surgical technique and outcomes

Abstract: The gold standard treatment for stress urinary incontinence (SUI) is the autologous rectus fascia pubovaginal sling. Although successful, it is associated with increased morbidity related to the graft harvest. Because of this, less invasive techniques were developed, including the retropubic and trans-obturator midurethral sling and the bone-anchored sling (BAS). Early reported outcome failures and concern for bone-anchored-related complications caused BAS to fall out of favor. However, technique modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…According to a 4-year follow-up study [58], with a high rate of early and late reported outcome failures, BAS fell out of favor. Although postoperative osteomyelitis is rare, each case incurs a substantial morbidity and a complicated postoperative course Therefore, the BAS procedure cannot be proposed for correction of SUI [58][59][60]. The estimated incidence of osteomyelitis after bone-anchored bladder neck suspension was 1.3% [59].…”
Section: Bone-anchored Slingsmentioning
confidence: 99%
“…According to a 4-year follow-up study [58], with a high rate of early and late reported outcome failures, BAS fell out of favor. Although postoperative osteomyelitis is rare, each case incurs a substantial morbidity and a complicated postoperative course Therefore, the BAS procedure cannot be proposed for correction of SUI [58][59][60]. The estimated incidence of osteomyelitis after bone-anchored bladder neck suspension was 1.3% [59].…”
Section: Bone-anchored Slingsmentioning
confidence: 99%
“…BAS were mainly used for indications of intrinsic sphincter deficiency and in patients who had failed previous anti-incontinence procedures as a salvage procedure (1). While they are effective (2) and associated with a minimal risk of complication (2), the high cost of bone anchoring devices and reports of poor success (3) have likely contributed to the decreased usage of the BAS.…”
Section: Introductionmentioning
confidence: 99%
“…Success rates of BAS in the literature are extremely variable and range from 60.4 to 94% (2,3). Unfortunately, many previous studies report conglomerate results of different sling materials with bone anchors despite evidence that the biomechanical material properties, such as strength and host durability, differ substantially (4).…”
Section: Introductionmentioning
confidence: 99%